A abordagem intertextual entre cultura de massa e literatura - Gomes Junior, Edmundo (2019)
This thesis aims to demonstrate how intertextuality can and should be used as a teaching tool, not only in Literature, but also within an interdisciplinary proposal that seeks multiple literacy. In order to accomplish that we propose the use of references belonging to the several manifestations of popular culture, among them productions defined as kitsch, such as comic books, memes and movies. Since students consume narratives in those media, through intertextuality we seek common ground between high literature and popular culture. One of the matching points of these seemingly dichotomous contexts is in religious kitsch, present in both Marvel Comics and in literary productions, including José Saramago's novel Blindness. The reading of images, both in the comic books and in the novel allows identifying the intersection of other texts, exemplifying the concept of intertextuality defined by Julia Kristeva. These practices demonstrate that intertextual exercises can aid teaching approaches as a tool to approximate the fictional universe of the student and the teacher, valuing the identities of individuals. We propose that the reading of comics does not seek to replace the reading of literary works, and in this sense, we present, instead of adaptations of these works in comic books, the analysis of the ones better known by the common public, recognizing their appeal among the youngster. The identification of intertextual elements such as parody and pastiche in kitsch productions helps to recognize them in high literature, which allows a more pleasant reading of works which are considered complex.